A composite compatibilizer for wood-plastic materials and its preparation process

By using an improved composite compatibility preparation process in wood-plastic composites, the problems of low grafting rate and serious polypropylene degradation are solved, and higher compatibility and performance improvements are achieved.

CN119192483BActive Publication Date: 2025-02-18DALIAN HENGTAI HENGBAO PLASTIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411322501.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-18
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The grafting rate of the compatibility agent used in existing wood-plastic composite materials is low, resulting in severe degradation of polypropylene and cannot effectively improve the compatibility of wood powder and plastic.

Method used

Using a composite compatibilizer whose composition includes polyolefins, functional monomers, solvents, initiators, processing aids and additives, through specific preparation processes such as swelling treatment, preparation of hydroxyl-modified nanosilicon dioxide Co-graft modification with melt increases the grafting rate of maleic anhydride and inhibits the degradation of polypropylene.

Benefits of technology

It improves the grafting rate of maleic anhydride, improves the compatibility between wood powder and plastic, reduces the degradation of polypropylene, and significantly improves the performance of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a composite compatibilizer for wood-plastic materials and a preparation process thereof, belonging to the technical field of polymer chemistry. It includes swelling polyolefin with xylene solvent; mixing polyolefin: 120-150 parts, functional monomer: 9-17 parts, solvent: 2-3 parts, initiator: 0.1-0.5 parts, processing aid: 1-2 parts, additive: 3-5 parts, and feeding into a twin-screw extruder by side feeding, then applying ultrasonic treatment, performing melt grafting extrusion granulation, and obtaining a composite compatibilizer. The present invention adopts maleic anhydride and divinylbenzene to perform melt co-grafting modification on polypropylene. In the co-grafting reaction system, divinylbenzene is grafted before the free radical rupture of the polypropylene macromolecular chain, and plays a role in stabilizing free radicals, and then copolymerization grafting and coupling chain extension occur, thereby inhibiting the degradation of polypropylene, and also promoting the copolymerization grafting and branching reaction of maleic anhydride, thereby improving the grafting rate of maleic anhydride.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer chemistry, in particular to a composite compatibilizer for wood-plastic materials and a preparation process thereof. Background Art

[0002] Wood-plastic composite materials, referred to as WPC, are a new type of composite materials that are made of powdered or fibrous biomass materials and thermoplastics, and are processed by extrusion, injection molding and hot pressing. WPC combines the excellent properties of thermoplastics and biomass materials. It can be recycled and reused many times after being discarded, and is a typical environmentally friendly material. The commonly used biomass materials for WPC mainly include wood powder, shavings and other wood processing scraps, as well as fast-growing crops and plant fibers; the commonly used plastic matrix is ​​mainly new materials and recycled materials of general thermoplastics such as polypropylene (PP), polyethylene (PE), and polyvinyl chloride (PVC). The development of WPC can alleviate the problem of global wood resource scarcity and open up new ways for the high-value-added reuse of discarded biomass materials and waste plastics. As an emerging green and environmentally friendly industry, WPC products have been widely used in construction, interior decoration, automotive interiors, municipal facilities, packaging and transportation, and other fields.

[0003] Since wood powder contains a large amount of hydroxyl groups, it is hydrophilic; while most plastic resins such as polyethylene, polypropylene, and polyvinyl chloride are non-polar or have very low polarity, so they are hydrophobic; therefore, the interfacial bonding force between the two is very poor. How to improve the dispersibility of wood powder and enhance the compatibility of the two phases is the research topic of a large number of literatures.

[0004] At present, the compatibilizers used in wood-plastic composite materials are mainly products of various polyolefins grafted with maleic anhydride, such as polypropylene grafted with maleic anhydride (PP-g-MAH). Grafting maleic anhydride on the PP chain can increase polarity. At present, the preparation of PP-g-MAH by the melt method has been industrialized, and most of the PP-g-MAH on the market is produced by the melt method. The melt method has many advantages, such as simple post-treatment and continuous production, but the disadvantages of the melt method also exist. Most of the melt grafting uses peroxide initiators, which makes the macromolecular free radicals not only graft when participating in the reaction, but also cause a series of side reactions, including chain scission, degradation, chain transfer, coupling termination, etc., which makes the grafted product (PP-g-MAH) have a low grafting rate, a large amount of maleic anhydride residue, and serious degradation of polypropylene.

[0005] Therefore, the present application provides a composite compatibilizer for wood-plastic materials and a preparation process thereof, which can improve the grafting rate of maleic anhydride and inhibit the degradation of polypropylene, to meet the needs. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a composite compatibilizer for wood-plastic materials and a preparation process thereof, so as to solve the problems of low grafting rate and serious degradation of polypropylene in existing grafted materials.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A composite compatibilizer for wood-plastic materials, the components and weight fractions of which are:

[0009] Polyolefin: 120-150 parts,

[0010] Functional monomer: 9-17 parts,

[0011] Solvent: 2-3 parts,

[0012] Initiator: 0.1-0.5 parts,

[0013] Processing aids: 1-2 parts,

[0014] Additives: 3-5 parts;

[0015] Wherein, the solvent is a composite of epoxidized soybean oil and blending oil;

[0016] The preparation process of the composite compatibilizer comprises the following steps:

[0017] S1: Swelling treatment of polyolefin with xylene solvent;

[0018] S2: adding 0.2-0.3 parts by weight of L-arginine to 170-180 parts by weight of deionized water, stirring and mixing at room temperature, adding 20-23 parts by weight of tetraethyl silicate and 3-5 parts by weight of SiO2, stirring and mixing evenly, and reflux reaction at 80-85° C. for 24-25 hours to obtain a dispersion of hydroxyl-modified nano-silicon dioxide;

[0019] S3: The dispersion of hydroxyl-modified nano-silica is concentrated by rotary evaporation to 1 / 10-1 / 8 of the original, transferred to a dialysis membrane with a molecular weight cutoff of 3000, dialyzed with deionized water for 24-25 hours, and finally rotary evaporated to dryness and vacuum dried to obtain hydroxyl-modified ultrafine silica;

[0020] S4: dissolving a composite of functional monomers maleic anhydride and divinylbenzene, initiator epoxy soybean oil and blending oil in a water bath at 50-60°C, adding a processing aid styrene and an additive hydroxyl-modified ultrafine silica, stirring evenly at room temperature, adding to the swollen polyolefin, stirring and dispersing, and then adding to a high-speed mixer and mixing for 3-5 minutes to obtain a premix;

[0021] S5: feeding the premix into a twin-screw extruder by side feeding, extruding the premix by the twin-screw extruder, and then subjecting the premix to ultrasonic treatment, performing melt grafting extrusion granulation, and obtaining a composite compatibilizer;

[0022] The specific parameters in step S5 are processing temperature of 160-200° C., screw speed of 500-700 r / min, and ultrasonic power of 500-700 W.

[0023] Optionally, the polyolefin may be one of polyethylene, polypropylene, and a composite of any combination of the above components.

[0024] Optionally, the weight ratio of maleic anhydride to divinylbenzene is 8-15:1-2.

[0025] Optionally, the weight ratio of the epoxidized soybean oil to the blending oil is 1:2-3.

[0026] Optionally, the initiator is one of benzoyl peroxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, and a complex formed by any combination of the above components.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects:

[0028] 1. The present invention modifies silicon dioxide to obtain hydroxyl-modified nano-silica. The hydroxyl-modified nano-silica has better dispersibility in a polypropylene matrix. The hydroxyl group can produce a weak interaction with certain functional groups on the polypropylene molecular chain, so that the hydroxyl-modified nano-silica is evenly distributed in the polypropylene, providing more reaction sites for the grafting of maleic anhydride. In addition, during the grafting reaction, the hydroxyl group can interact with the maleic anhydride, prompting the maleic anhydride to approach the polypropylene molecular chain, thereby improving the grafting reaction and then effectively improving the grafting rate.

[0029] 2. The present invention uses xylene to swell polypropylene in advance, which can effectively improve the uniform dispersion of maleic anhydride monomer and polypropylene, improve the dispersion problem of maleic anhydride in polypropylene, and dissolve functional monomers by epoxidized soybean oil / blending oil, which can effectively inhibit monomer volatilization and increase the monomer concentration of the reaction system. When using epoxidized soybean oil and blending oil, adding styrene can increase the grafting rate of maleic anhydride to polypropylene, and adding styrene can also reduce the degradation of polypropylene to a certain extent.

[0030] 3. The present invention adopts maleic anhydride and divinylbenzene to perform melt co-grafting modification on polypropylene. In the co-grafting reaction system, divinylbenzene is grafted before the free radical breakage of the polypropylene macromolecular chain, and plays a role in stabilizing the free radical, and then copolymerization grafting and coupling chain extension occur, thereby inhibiting the degradation of polypropylene, and at the same time, it also promotes the copolymerization grafting and branching reaction of maleic anhydride, thereby improving the grafting rate of maleic anhydride. DETAILED DESCRIPTION

[0031] The following is a detailed description of a composite compatibilizer for wood-plastic materials and its preparation process provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies.

[0032] It should be noted that the references to "one embodiment", "embodiment", "exemplary embodiments", "some embodiments" and the like in the specification indicate that the embodiments described may include specific features, structures or characteristics, but not every embodiment may include the specific features, structures or characteristics. In addition, when a specific feature, structure or characteristic is described in conjunction with an embodiment, it should be within the knowledge of a person skilled in the art to implement such feature, structure or characteristic in conjunction with other embodiments (whether or not explicitly described).

[0033] Example 1

[0034] A composite compatibilizer for wood-plastic materials and a preparation process thereof, comprising the following steps:

[0035] S1: adding 120 parts by weight of polypropylene to 200 parts by weight of xylene solvent, stirring and mixing evenly, and sealing with plastic wrap for 24 hours to obtain polypropylene after swelling treatment;

[0036] S2: Add 0.2 parts by weight of L-arginine to 170 parts by weight of deionized water, stir and mix at room temperature, then add 20 parts by weight of tetraethyl silicate and 3 parts by weight of SiO2, stir and mix evenly, then reflux at 80° C. for 24 hours to obtain a dispersion of hydroxyl-modified nano-silica;

[0037] S3: The dispersion of hydroxyl-modified nano-silica was concentrated to 1 / 10 of the original by rotary evaporation, transferred to a dialysis membrane with a molecular weight cutoff of 3000, dialyzed with deionized water for 24 hours, and finally rotary evaporated to dryness and vacuum dried to obtain hydroxyl-modified ultrafine silica;

[0038] S4: 8 parts by weight of maleic anhydride, 1 part by weight of divinylbenzene, 0.1 part by weight of diisopropylbenzene peroxide, 2 parts by weight of epoxy soybean oil and blending oil are dissolved in a 50°C water bath, the weight ratio of epoxy soybean oil to blending oil is 1:2, and hot stirring is continuously performed during the dissolution process. After complete dissolution, 1 part by weight of styrene and 3 parts by weight of hydroxyl-modified ultrafine silica are added, stirred at room temperature, and after stirring evenly, added to 120 parts by weight of swollen polypropylene and stirred for pre-dispersion, and then added to a high-speed mixer and mixed for 3 minutes to obtain a premix;

[0039] S5: The premix is ​​fed into a twin-screw extruder by side feeding, extruded by the twin-screw extruder, and then subjected to ultrasonic treatment, wherein the specific parameters are processing temperature at 160° C., screw speed at 500 r / min, and ultrasonic power at 500 W, and melt grafting extrusion granulation is performed to obtain a composite compatibilizer.

[0040] Example 2

[0041] A composite compatibilizer for wood-plastic materials and a preparation process thereof, comprising the following steps:

[0042] S1: adding 150 parts by weight of polypropylene to 230 parts by weight of xylene solvent, stirring and mixing evenly, and sealing with plastic wrap for 24 hours to obtain polypropylene after swelling treatment;

[0043] S2: Add 0.3 parts by weight of L-arginine to 180 parts by weight of deionized water, stir and mix at room temperature, then add 23 parts by weight of tetraethyl silicate and 5 parts by weight of SiO2, stir and mix evenly, then reflux at 80° C. for 24 hours to obtain a dispersion of hydroxyl-modified nano-silica;

[0044] S3: The dispersion of hydroxyl-modified nano-silica was concentrated to 1 / 8 of the original volume by rotary evaporation, and then transferred to a dialysis membrane with a molecular weight cutoff of 3000, and dialyzed with deionized water for 24 hours, and finally rotary evaporated to dryness and vacuum dried to obtain hydroxyl-modified ultrafine silica;

[0045] S4: Dissolve 15 parts by weight of maleic anhydride, 2 parts by weight of divinylbenzene, and 0.5 parts by weight of diisopropylbenzene peroxide with 3 parts by weight of epoxy soybean oil and blending oil in a 50°C water bath, wherein the weight ratio of epoxy soybean oil to blending oil is 1:3. Heat stirring is continuously performed during the dissolution process. After complete dissolution, add 2 parts by weight of styrene and 5 parts by weight of hydroxyl-modified ultrafine silica, stir at room temperature, stir evenly, add to 150 parts by weight of swollen polypropylene, stir and pre-disperse, and then add to a high-speed mixer and mix for 3 minutes to obtain a premix;

[0046] S5: The premix is ​​fed into a twin-screw extruder by side feeding, extruded by the twin-screw extruder, and then subjected to ultrasonic treatment, wherein the specific parameters are processing temperature at 160° C., screw speed at 500 r / min, and ultrasonic power at 500 W, and melt grafting extrusion granulation is performed to obtain a composite compatibilizer.

[0047] Example 3

[0048] A composite compatibilizer for wood-plastic materials and a preparation process thereof, comprising the following steps:

[0049] S1: adding 120 parts by weight of polypropylene to 200 parts by weight of xylene solvent, stirring and mixing evenly, and sealing with plastic wrap for 25 hours to obtain polypropylene after swelling treatment;

[0050] S2: Add 0.2 parts by weight of L-arginine to 170 parts by weight of deionized water, stir and mix at room temperature, then add 20 parts by weight of tetraethyl silicate and 3 parts by weight of SiO2, stir and mix evenly, then reflux at 85° C. for 25 hours to obtain a dispersion of hydroxyl-modified nano-silica;

[0051] S3: The dispersion of hydroxyl-modified nano-silica was concentrated to 1 / 10 of the original by rotary evaporation, transferred to a dialysis membrane with a molecular weight cutoff of 3000, dialyzed with deionized water for 25 hours, and finally rotary evaporated to dryness and vacuum dried to obtain hydroxyl-modified ultrafine silica;

[0052] S4: 8 parts by weight of maleic anhydride, 1 part by weight of divinylbenzene, 0.1 part by weight of diisopropylbenzene peroxide, 2 parts by weight of epoxy soybean oil and blending oil are dissolved in a 60°C water bath, the weight ratio of epoxy soybean oil to blending oil is 1:2, and hot stirring is continuously performed during the dissolution process. After complete dissolution, 1 part by weight of styrene and 3 parts by weight of hydroxyl-modified ultrafine silica are added, stirred at room temperature, and after stirring evenly, added to 120 parts by weight of swollen polypropylene and stirred for pre-dispersion, and then added to a high-speed mixer and mixed for 5 minutes to obtain a premix;

[0053] S5: feeding the premix into a twin-screw extruder by side feeding, extruding the premix by the twin-screw extruder, and then applying ultrasonic treatment, wherein the specific parameters are processing temperature at 200°C, screw speed at 700r / min, and ultrasonic power at 700W, and performing melt grafting extrusion granulation to obtain a composite compatibilizer.

[0054] Comparative Example 1

[0055] Compared with Example 1, the difference of Comparative Example 1 is that, in Comparative Example 1, divinylbenzene in step S4 is removed, and the other steps remain unchanged to prepare the composite compatibilizer, which is recorded as Comparative Example 1.

[0056] Comparative Example 2

[0057] Compared with Example 1, the difference of Comparative Example 2 is that in Comparative Example 2, the epoxidized soybean oil and the blending oil in step S4 are replaced with acetone of equal mass, and the other steps remain unchanged to prepare the composite compatibilizer, which is recorded as Comparative Example 2.

[0058] Comparative Example 3

[0059] Compared with Example 1, the difference of Comparative Example 3 is that, in Comparative Example 3, styrene in step S4 is removed, and the other steps remain unchanged to prepare the composite compatibilizer, which is recorded as Comparative Example 3.

[0060] Comparative Example 4

[0061] Compared with Example 1, the difference of Comparative Example 4 is that the hydroxyl-modified ultrafine silica in step S4 is removed, and the other steps remain unchanged to prepare the composite compatibilizer, which is recorded as Comparative Example 4.

[0062] Comparative Example 5

[0063] Compared with Example 1, the difference of Comparative Example 5 is that, in Comparative Example 4, steps S2-S3 are removed, the hydroxyl-modified ultrafine silica in S4 is replaced with an equal weight portion of silica, and the remaining steps remain unchanged to prepare the composite compatibilizer, which is recorded as Comparative Example 5.

[0064] Comparative Example 6

[0065] Compared with Example 1, the difference of Comparative Example 6 is that Comparative Example 6 removes step S1, replaces the polypropylene after swelling treatment in step S4 with an equal weight of polypropylene, and replaces 1 weight part of styrene and 3 weight parts of hydroxyl-modified ultrafine silica with 1 weight part of styrene, 1 weight part of xylene and 3 weight parts of hydroxyl-modified ultrafine silica, and the remaining steps remain unchanged to prepare a composite compatibilizer, which is recorded as Comparative Example 6.

[0066] The grafting rate of the composite compatibilizers prepared in Examples 1-3 and Comparative Examples 1-6 was measured. The measurement results are shown in Table 1.

[0067] Table 1. Grafting rate measurement results of Examples 1-3 and Comparative Examples 1-6

[0068]

[0069] It can be seen from the data in Table 1 that the data of Comparative Example 1 is significantly lower than that of the embodiment, indicating that the grafting rate of maleic anhydride can be improved by melt co-grafting modification of polypropylene with maleic anhydride and divinylbenzene; the data of Comparative Examples 2 and 3 are both lower than that of the embodiment, indicating that the addition of styrene can improve the grafting rate of maleic anhydride on polypropylene when epoxy soybean oil and blending oil are used; the data of Comparative Examples 4 and 5 are lower than that of the embodiment, indicating that the addition of hydroxyl-modified ultrafine silica can improve the grafting rate of maleic anhydride on polypropylene and is better than silica, and the data of Comparative Example 6 is lower than that of the embodiment, indicating that swelling treatment of polypropylene first can improve the grafting rate of maleic anhydride on polypropylene compared with directly adding xylene to the reaction system.

[0070] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A composite compatibilizer for wood-plastic materials, characterized in that: The components and weight fractions are: Polyolefin: 120-150 parts, Functional monomer: 9-17 parts, Solvent: 2-3 parts, Initiator: 0.1-0.5 parts, Processing aids: 1-2 parts, Additives: 3-5 parts; Wherein, the solvent is a composite of epoxidized soybean oil and blending oil; The preparation process of the composite compatibilizer comprises the following steps: S1: Swelling treatment of polyolefin with xylene solvent; S2: adding 0.2-0.3 parts by weight of L-arginine to 170-180 parts by weight of deionized water, stirring and mixing at room temperature, adding 20-23 parts by weight of tetraethyl silicate and 3-5 parts by weight of SiO2, stirring and mixing evenly, and reflux reaction at 80-85° C. for 24-25 hours to obtain a dispersion of hydroxyl-modified nano-silicon dioxide; S3: The dispersion of hydroxyl-modified nano-silica is concentrated by rotary evaporation to 1 / 10-1 / 8 of the original, transferred to a dialysis membrane with a molecular weight cutoff of 3000, dialyzed with deionized water for 24-25 hours, and finally rotary evaporated to dryness and vacuum dried to obtain hydroxyl-modified ultrafine silica; S4: dissolving a composite of functional monomers maleic anhydride and divinylbenzene, initiator epoxy soybean oil and blending oil in a water bath at 50-60°C, adding a processing aid styrene and an additive hydroxyl-modified ultrafine silica, stirring evenly at room temperature, adding to the swollen polyolefin, stirring and dispersing, and then adding to a high-speed mixer and mixing for 3-5 minutes to obtain a premix; S5: feeding the premix into a twin-screw extruder by side feeding, extruding the premix by the twin-screw extruder, and then subjecting the premix to ultrasonic treatment, performing melt grafting extrusion granulation, and obtaining a composite compatibilizer; The specific parameters in step S5 are processing temperature of 160-200° C., screw speed of 500-700 r / min, and ultrasonic power of 500-700 W.

2. A composite compatibilizer for wood-plastic materials according to claim 1, characterized in that: The polyolefin may be polyethylene, polypropylene, or a composite of any combination of the above components.

3. The composite compatibilizer for wood-plastic materials according to claim 1, characterized in that: The weight ratio of maleic anhydride to divinylbenzene is 8-15:1-2.

4. The composite compatibilizer for wood-plastic materials according to claim 1, characterized in that: The weight ratio of the epoxidized soybean oil to the blending oil is 1:2-3.

5. The composite compatibilizer for wood-plastic materials according to claim 1, characterized in that: The initiator is one of benzoyl peroxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, and a composite formed by any combination of the above components.

Citation Information

Patent Citations

  • Method for preparing polypropylene / maleic anhydride melt grafting high condensing pre-mixed master batch

    CN101423590A

  • Grafted modified polypropylene wood-plastic composite material and preparation method thereof

    CN106519556A